Value of Health, Life, Freedom and Economic Stabilization at the Early Stage of the COVID-19 Pandemic in Poland: According to Students of the University of Rzeszów - Garwol, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article attempts to answer the question of the approach of students at the University of Rzeszów to the values ​​of health, life, freedom and economic stabilization during the restrictions on movement and maintaining social contacts introduced at the beginning of the SARS-CoV-2 coronavirus pandemic. The introduction describes the characteristics of the SARS-CoV-2 coronavirus pandemic and the COVID-19 disease it causes. Then, a selective overview of Polish research on the social aspects of the pandemic conducted at its beginning, from March to May 2020, is presented. The next section presents the results of own research, divided into those concerning the perception of the current situation by the respondents and their predictions for the future. The purpose of the article was to review the results of existing research and to find out about the opinions of students on the given issues.